EVOLUZIONE MOLECOLARE DELLE METALLOTIONEINE NEI NOTOTHENIOIDEI ANTARTICI - BAKIU, RIGERS (Università degli studi di Padova, 2010)
Metallothioneins (MTs) are low-molecular weight (6-18 kDa) and sulphur-rich proteins. These proteins have been identified in animals, plants and in both eukaryotic and prokaryotic microorganisms. MTs are involved in the homeostasis of essential metals as well as in the detoxification of the non essential ones. Furthermore they act as scavengers of reactive oxygen species (ROS). This work is part of wider studies on evolutionary aspects of MTs in teleosts. The molecular evolution of MTs in the Antarctic Notothenioid has been investigated. MT cDNA sequences of some members of Nototheniidae, Bathydraconidae, Artedidraconidae and Channichthyidae families have been characterised and evolutionary aspects have been inferred. Maximum likelihood (ML) and Bayesian methods were applied to the coding and UTR sequences. The results indicate the presence of two MT groups, each containing one of the two isoforms, MT-1 and MT-2. Likelihood tests (LH) results support the hypothesis that molecular evolution of notothenioid MTs is based on relaxed clock model. Several discrepancies (mismatches) were observed between MT gene genealogy and species phylogeny. On the basis of these mismatches analyses have been preformed in order to evaluate if positive selection could have been acted. The data indicate the absence of positive selection and suggest the presence of a strong purifying selection operating at the amino acidic level. In addition, phylogenetic analyses on UTRs indicate that 5' UTRs could have been evolved differently from 3' UTRs. Only the 3'UTR of both Notothenia coriiceps MT-1 and Cygnodraco mawsoni MT-2 could have been undergone to convergence events. Furthermore, some MT introns and promoter sequences were characterised. The phylogenetic analyses, based on these sequences, suggest they could be more useful than cDNAs in the study of molecular evolution of notothenioids MTs. These results showed that introns could be generally utilised in evolutionary analyses of nuclear genes. Le metallotioniene (MT) sono proteine dal ...